The badge, the blazer and those who came before us: a sociological study on hazing in former model C all-boys schools in the Eastern Cape - Gobodo, Bapiwe (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch Unviersity, 2022.